Dynamic stochastic general equilibrium model in international finance : inflation inertia in a small open economy model - Teo, Jansen Tiu. (2009)
The dynamic stochastic general equilibrium (DSGE) framework of an economy allows researchers to simulate and estimate, in response to a shock, the dynamic interplay of hundreds of variables in an economy. In particular, understanding the dynamic effects of a shock on aggregate inflation is of paramount importance for macroeconomists and central bankers. In a theoretical model, inflation is represented as a function of inflation expectations and the output gap. This equation is called the “new Keynesian Phillips curve” or NKPC. Traditionally, the foundation of the NKPC is the Calvo sticky price model. In spite of being widely used, the Calvo sticky price model has several flaws. The most important limitation is the issue with inflation inertia. Although price level is sticky, the theoretical model fails to show the inertial behaviour of aggregate inflation that is observed empirically when there is a monetary policy shock. Subsequently, this gave rise to a new school of thought in recent years, led by Mankiw and Reis who showed that the sticky information model that they have created resolves the inflation inertia issue. While sticky information successfully models the inertial behavior of inflation in response to a shock, it is not without important limitations. The most crucial of which is that the Mankiw-Reis model is based on a highly stylised partial equilibrium model wherein they make an arguable assumption that demand is exogenously set. Most recently, Christiano, Eichenbaum, and Evans proposed a new model called the hybrid sticky price-sticky information NKPC. In this project, I lay out the sticky price, sticky information, and hybrid model through the use of mathematics. Next, I explain their respective limitations and implications. With the ultimate objective as being able to theoretically show inflation inertia, I incorporate information stickiness into Gali and Monacelli’s DSGE framework of a small open economy. I show that by using a hybrid NKPC instead of the standard Calvo NKPC, the inertial behavior of aggregate inflation in response to a shock can be simulated in Gali and Monacelli’s DSGE framework.